Traditional justice and community mediation: a comparative analysis of dispute resolution in Pakistan and the USA - Ullah Khan, Ihtesham; Mohamed, Nurah Sabahiah; Ullah, Nazir (The Grand Asian Law Journal (GALJ), 2025)
Disputes are ubiquitous in human societies, occurring among individuals, families, tribes, and nations. In Pakistan, various provinces have developed traditional dispute resolution mechanisms: the Jirga system for the Pashtoon community, Panchayat for Punjabis, Faislo among Sindhis, and the Balochi Jirga for Balochis. Rooted in cultural practices, these systems have historically facilitated justice and social harmony. However, they have faced criticism for relying on unwritten rules, informal structures, and for perpetuating human and women’s rights violations. This article examines the nature of these traditional systems in Pakistan, analysing their dispute resolution methods and effectiveness in administering justice. It also proposes recommendations for improving these systems, drawing insights from the USA’s successful community mediation programs. Unlike Pakistan, the USA has formalised community mediation under the National Association for Community Mediation, achieving notable success in conflict resolution. The study adopts a qualitative methodology, employing doctrinal and library-based legal research, along with a comparative analysis of community dispute resolution in Pakistan and the USA. The article suggests that Pakistan should establish a legal framework to regulate community mediation, ensuring adherence to human rights and justice standards. By integrating lessons from the USA’s approach and emphasising the role of government bodies in justice administration, traditional dispute resolution systems in Pakistan can be strengthened for greater effectiveness and fairness in resolving disputes.